Sailors and Shelves: Renewing the Library at the Maritime Museum of British Columbia - Vis, Brittany (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2013)
This article examines the library collection at the Maritime Museum of British Columbia. It provides portraits of its collections and outlines their importance for maritime, genealogical, scholarly, and general interest researchers. As a little-known collection in an underfunded cultural institution, this library has not received the financial support it deserves and is thus confronting the deterioration of its artifacts. The museum board members and the collections manager have launched an initiative to fully catalogue and preserve the entire library. This article outlines their approach, which serves as an example for similar institutions.